Public Policy Construction In The Framework Of Value Realization And Election Political Analysis - Sua Fauzan Fataruba; Tri Sosilowati (Universitas Sains dan Teknologi Komputer, 2023)
This research is research that is used to analyze the extent to which political values influence social society. As we all understand, the Indonesian nation will soon hold an election procession in 2024. So many political parties have implemented an approach with the people, as their constituents. Based on these problems, this research was carried out. This research method emphasizes normative legal analysis combined with a conceptual approach and qualitative analysis. The results of this research are that political values have experienced concrete degradation, resulting in elections being limited to a recurring 5-year routine. Such conditions certainly have a broad impact on Indonesian democracy. The suggestions that can be given in this research are about how the construction of political parties can be revitalized towards a much more progressive aspect. This progressivism will be the added value and the value that differentiates democratic rationality and political egocentrism.